SOCIAL AND PHILOSOPHICAL CONTENT OF AN INCLUSIVE SOCIETY (Scientific journal of the Fergana State University, 2026)
The article analyzes the content of the concept of an inclusive society and a number of scientific and theoretical approaches to it based on information published in foreign and domestic publications. As part of the scientific research, one of the main tasks was to conduct a socio-philosophical analysis of an inclusive society based on scientific theories and empirical approaches. In addition, the article examines foreign and domestic experience in the development of an inclusive society and the application of inclusive education models in Uzbekistan. The tasks were set to study the features and socio-philosophical aspects of an inclusive society in the context of globalization, as well as the development of practical recommendations and proposals through empirical research.